Pengaruh Penerapan Teori Bruner Berbantuan Media Block Dienes Terhadap Hasil Belajar Siswa Materi Pembagian Kelas III - Riska Rinanda; Fauzi Fauzi; Ahadin Ahadin (Elementary Education Research, 2023)
The aim of the study was to determine the effect of applying Bruner's theory assisted by Dienes Block Media on student learning outcomes in class III division material at SDN 53 Banda Aceh. This research takes a quantitative approach, the type of research is True-Experimental Design. The research design is Pretest-Posttest Control Group Design. The research was conducted at SDN 53 Banda Aceh. The sample in this study was students in class III B as the experimental class and class III C as the control class, both classes totaling 25 people. The research instrument is in the form of essay questions as many as 7 questions. Data collection techniques namely pre-test and post-test. Data analysis techniques used IBM SPSS 26 and hypothesis testing through the Independent Sample Test t-test statistic with a significance value (2-tailed) of 0.000 0.05 meaning that Ha is accepted and Ho is rejected. So the final conclusion is that there is a significant influence on the application of Bruner's theory assisted by Block Dienes Media on student learning outcomes in class III division material at SDN 53 Banda Aceh.